Determinant Factors Of The Centrifugal and Centripetal Movement Of People To The Urban Fringe Areas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Keyword : Determinant Factors, Centripetal Movement